CONCEPTUAL APPROACHES TO MANAGING THE FORMATION OF A COMPETITIVE STRATEGY OF AN ENTERPRISE AND PRACTICAL ASPECTS OF THEIR APPLICATION IN THE MODERN BUSINESS ENVIRONMENT (Development Service Industry Management, 2024)
The paper summarizes the conceptual framework for the formation of a competitive strategy, and based on the results of the study, clarifies the definition of a competitive strategy of a business organization as an economic category and identifies its specific features. It is substantiated that an effective competitive strategy should reflect the peculiarities of managerial mindset and understanding of business, as well as the nature of the business organization’s response to changes in the factors of the external and internal environment. Accordingly, a typology of managerial approaches to the formation of a competitive strategy (reactive, active and proactive) is developed and the key characteristics of each approach are identified.The features of generic competitive strategies are outlined, and the risks and limitations of their implementation in the context of modern business organizations are supplemented. The essence of hybrid competitive strategies is considered and the key success factors for their implementation are summarized. Based on the findings of the study it can be concluded that the choice of a particular type of competitive strategy depends on the specifics of the industry and the stage of its life cycle, the level of competition intensity, current market position, available resources, competencies and strategic goals of an organization, as well as the type of managerial mindset and the way the company responds to changes in the business environment.
Keywords: strategy; competitive strategy; competitiveness; sustainable competitive advantage; business organization; business environment; competitiveness management